2015
DOI: 10.1007/s00198-015-3422-5
|View full text |Cite
|
Sign up to set email alerts
|

Higher levels of s-RANKL and osteoprotegerin in children and adolescents with type 1 diabetes mellitus may indicate increased osteoclast signaling and predisposition to lower bone mass: a multivariate cross-sectional analysis

Abstract: T1DM children and adolescents have impaired bone metabolism which seems to be multifactorial. Reduced osteoblast and increased osteoclast signaling, resulting from multiple simultaneous disturbances, could lead to reduced peak bone accrual in early adulthood, predisposing to adult osteopenia and osteoporosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
62
3
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(71 citation statements)
references
References 47 publications
3
62
3
1
Order By: Relevance
“…Our finding also showed no differences in P1NP levels between diabetes patients with or without micro-vascular complications [27]. In contrast to our study, Shanbhogue and colleagues have reported higher level of P1NP in T2DM with or without micro-vascular complications compared to respective controls [26].…”
Section: Discussioncontrasting
confidence: 83%
“…Our finding also showed no differences in P1NP levels between diabetes patients with or without micro-vascular complications [27]. In contrast to our study, Shanbhogue and colleagues have reported higher level of P1NP in T2DM with or without micro-vascular complications compared to respective controls [26].…”
Section: Discussioncontrasting
confidence: 83%
“…In this mechanism, OPG appears to act as a negative regulator of osteoclastogenesis. Recent data suggest that increased bone turnover may be associated with increased soluble RANKL (s-RANKL) activity, as seen in children and adolescents with T1D, which would promote increased osteoclast activity and bone resorption [93]. In support of this theory, it has been shown that peripheral blood derived osteoclasts from humans with T1D are less sensitive to OPG than osteoclasts from control subjects, indicating a heightened sensitivity in RANKL/RANK signaling [94].…”
Section: Effects Of T1d On Osteoclastsmentioning
confidence: 99%
“…Few studies have investigated the effects of T1D on vitamin D metabolism in humans. One study in young adults with T1D found no relationship between HbA1c and either 25(OH) vitamin D, 1,25(OH) 2 vitamin D, or 24,25(OH) 2 vitamin D [79]. Urinary vitamin D binding protein excretion was higher in T1D patients compared to controls, and related to hyperglycemia and urinary microalbumin excretion [80], a finding which could contribute to low-vitamin D levels in patients with poorly controlled or long-standing disease.…”
Section: Introductionmentioning
confidence: 99%